First steps toward gender equity in the chemistry Olympiad: Understanding the role of implicit gender‐science stereotypes. Issue 1 (14th June 2020) - Steegh, Anneke; Höffler, Tim; Höft, Lars; Parchmann, Ilka
Abstract: Girls are underrepresented in mathematical and science Olympiads, global informal learning activities which often serve as stepping stones for admission to top universities and future STEM careers. The present article aims to investigate the role of implicit gender‐science stereotypes on representation and achievement among participants of the German Chemistry Olympiad using a cross‐sectional online study ( N = 445, mean age 16.5 years, 51% female) entailing the Implicit Association Test and two motivational scales. This study was the first of its kind to use moderated mediation analysis to examine the effects of gender‐science stereotypes on participation and achievement, mediated by the expectancy and value beliefs self‐concept and topic interest. We found that in the female group, gender‐science stereotypes negatively predicted the participants' willingness to continue in the competition. This relationship was mediated through topic interest. In addition, we found self‐concept predictive for further participation among female participants, as well as for competition score among both gender groups. Furthermore, topic interest positively predicted male participants' willingness to continue with the competition. The results underline the negative association of implicit gender stereotypes with female participation in the German Chemistry Olympiad. Organizations such as the German Chemistry Olympiad should therefore critically reflect on existing gender biases within their own structure. In doing so they can create an environment that has the potential to heighten self‐concept and interest for all participants equally. Our findings add to existing expectancy‐value research in the context of gender differences in mathematics and science, supporting potential strategies toward gender equity.